Quartic exercises - Max-Albert Knus; Jean-Pierre Tignol (International Journal of Mathematics and Mathematical Sciences)
A correspondence between quartic étale algebras over a field and quadratic étale extensions of cubic étale algebras is set up and investigated. The basic constructions are laid out in general for sets with a profinite group action and for torsors, and translated in terms of étale algebras and Galois algebras. A parametrization of cyclic quartic algebras is given.